Effectiveness of Minkerrenka therapy on blood pressure reduction in menopausal women - Ernawati; Sulistyawati, Dwi; Nikki Susanti (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Hypertension is a condition where blood pressure exceeds normal levels and is one of the leading causes of death in Indonesia. Hypertension is characterized by a systolic blood pressure of more than 140 mmHg and a diastolic blood pressure of more than 90 mmHg. An increase in blood pressure can occur in both men and women, but the increase in blood pressure in older age is indeed more clearly or noticeably seen in women.This research is a quantitative study with a Quasi-Experiment pre & post test design with a Control group. The sample in this study consisted of 50 respondents, with 25 in the Intervention group and 25 in the Control group. The sampling in this study used purposive sampling. The data collected includes blood pressure measurements before and after the intervention of the MinHerRenKa Combination Therapy. Lowering Blood Pressure through foot soaking with warm water as therapy aims to improve blood circulation, reduce edema, enhance muscle relaxation, promote heart health, relieve stress, alleviate muscle stiffness, muscle pain, ease discomfort, increase capillary permeability, and provide warmth to the body, making it very beneficial for hypertension blood pressure reduction therapy. Combination Therapy of Herbal Drinks and Foot Soaking. In its implementation, the therapy is not just about providing herbal drinks and foot soaking, but also involves the methods and techniques of making herbal drinks and the steps for foot soaking, which have been proven effective in lowering blood pressure.